DETERMINANTS OF THE CURRENT ACCOUNT BALANCE IN TURKEY: AN ARDL APPROACH - Insel, Aysu; Kayikci, Fazil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
The objective of this paper is to examine the theoretical and empirical linkage between current account deficits and a broad set of macroeconomic variables in Turkey. This paper employs the Auto Regressive Distributed Lag (ARDL) model to specify the determinants of the current account in Turkey between 1987 and 2009. Results indicate that inflation affects the current account balance positively, whereas growth, openness, oil prices, and appreciation of the real exchange rate cause the current account balance to deteriorate.After any shock, it takes four quarters for the current account balance to return to its long-run equilibrium level.
Keywords: Current account; Balance of payments; ARDL; Boud Test; COUNTRIES; DEFICITS; TRADE; Business & Economics